1972
DOI: 10.1002/bip.1972.360111114
|View full text |Cite
|
Sign up to set email alerts
|

Volume effects in aqueous solutions of macromolecules containing non‐polar groups

Abstract: SynopsisSpecific volumes at 25' of aqueous solutions of poly (N-methyl acrylamide) and poly-(ethylene oxide) have been measured, and the data obtained is compared with corresponding data on low-molecular-weight compounds. The results support the notion, that the volrrme changes following the interaction between aliphatic groups and water are positive. They are discussed with particular reference to pressure effects on protein conformations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
15
0

Year Published

1975
1975
2002
2002

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(17 citation statements)
references
References 10 publications
2
15
0
Order By: Relevance
“…Others, however, have pointed out that the local concentration of side chains in an unfolded polypeptide is sufficiently high that deviations from ideal thermodynamic behavior would be expected to occur (9)(10)(11). In support of this, we note that some of the nonideal behavior may arise from the failure of water to gain access to the entire denatured macromolecular surface.…”
supporting
confidence: 69%
“…Others, however, have pointed out that the local concentration of side chains in an unfolded polypeptide is sufficiently high that deviations from ideal thermodynamic behavior would be expected to occur (9)(10)(11). In support of this, we note that some of the nonideal behavior may arise from the failure of water to gain access to the entire denatured macromolecular surface.…”
supporting
confidence: 69%
“…A possible explanation for this contradiction might be given if the local concentration of nonpolar groups exposed is quite high in protein systems and the volume change for the rupture of hydrophobic bonds is partly positive (Boje & Hvidt, 1972;Gekko & Noguchi, 1979). In fact, the volume changes for the transfer of water into organic solvents are known to be positive (Masterton & Seiler, 1968), although the transfer of nonpolar groups into water produces negative volume changes (Kauzmann, 1959).…”
Section: ( 5 )mentioning
confidence: 91%
“…Studies of protein stability by means of various spectroscopic techniques have shown that increasing pressure reduces the partial volume of the molecule through compression and conformational changes. Although matter is always compressible, electrostriction of charged and polar side chains, hydrophobic hydration, hydrogen bonds stabilization and the elimination of packing defects are considered to be the main causes for this volume change [9][10][11][12][13][14][15].The effects of pressure on hemeproteins have been the subject of numerous investigations. Optical absorption [16][17][18][19][20][21], fluorescence [22], FTIR [23-25], Raman [26], and NMR [27-29] spectroscopies, and laser flash photolysis [30-32] have all shown that pressures near 300 MPa leads to subtle local rearrangements of the protein structure and that some intermediate states preceding unfolding probably appear.Therefore, it is important to determine whether the modifications observed at the level of the active site of myoglobin [17,18,20,21,[26][27][28][29] and the reorganization of the secondary structure with an alteration of the electrostatic and hydrogen-bond array [23,24] are related to a change in the tertiary structure of the protein.In order to reply these questions we report here for the first time, the results of small-angle neutron scattering (SANS) experiments performed on myoglobin (Mb) under pressure.…”
mentioning
confidence: 99%
“…Studies of protein stability by means of various spectroscopic techniques have shown that increasing pressure reduces the partial volume of the molecule through compression and conformational changes. Although matter is always compressible, electrostriction of charged and polar side chains, hydrophobic hydration, hydrogen bonds stabilization and the elimination of packing defects are considered to be the main causes for this volume change [9][10][11][12][13][14][15].…”
mentioning
confidence: 99%